OUTCOMES OF CONGENITAL HYDRONEPHROSIS TREATED WITH ANDERSON–HYNES PYELOPLASTY VIA POSTERIOR LUMBAR APPROACH IN INFANTS UNDER 12 MONTHS (Vietnam Journal of Community Medicine, 2026)
Objective: To contribute to the evaluation of surgical outcomes of Anderson–Hynes pyeloplasty for ureteropelvic junction obstruction in children under 12 months of age.Subjects and Methods: A retrospective study of infants under 12 months who underwent Anderson–Hynes pyeloplasty via a posterior lumbar approach from January 2021 to December 2024 at the National Children’s Hospital.Results: From January 2021 to December 2024, 83 infants under 1 year of age were diagnosed with congenital hydronephrosis due to ureteropelvic junction obstruction and underwent Anderson–Hynes pyeloplasty via a posterior lumbar incision. Left-sided surgery was performed in 54/83 (65.1%); on the right-sided was 21/83 (25,3%); and 8/83 (9,6%) of patients was performed on both side. The mean preoperative anteroposterior renal pelvic diameter was 36.7 ± 11.3 mm. The mean age at surgery was 4.5 ± 3.2 months, and the mean operative time was 46.8 ± 25.7 minutes. No anastomotic leakage was reported. The average hospital stay was 3.5 days. Postoperative followup was conducted using ultrasound measurement of the anteroposterior renal pelvic diameter. The mean follow-up duration was 16.8 ± 8.7 months. The mean postoperative anteroposterior diameter decreased to 7.5 ± 4.2 mm. Three out of 83 patients required reoperation due to recurrent anastomotic stricture.Conclusion: Anderson–Hynes pyeloplasty via a posterior lumbar approach for the treatment of hydronephrosis in infants under 1 year of age yields favorable outcomes.
Keywords: hydronephrosis, Anderson–Hynes pyeloplasty, surgical posterior approach